A heterotypic tridimensional model to study the interaction of macrophages and glioblastoma in vitro - Gattas, María José (2021)
Background: Glioblastoma multiforme (GBM) is the most frequent and aggressive primary brain tumor, and macrophages account for 30–40% of its composition. Most of these macrophages derive from bone marrow monocytes playing a crucial role in tumor progression. Unraveling the mechanisms of macrophages-GBM crosstalk in an appropriate model will contribute to the development of specific and more successful therapies. We investigated the interaction of U87MG human GBM cells with primary human CD14+ monocytes or the THP-1 cell line with the aim of establishing a physiologically relevant heterotypic culture model. Methods: primary monocytes and THP-1 cells were cultured in the presence of U87MG conditioned media or co-cultured together with previously formed GBM spheroids. Monocyte differentiation was determined by flow cytometry. Results: primary monocytes differentiate to M2 macrophages when incubated with U87MG conditioned media in 2-dimensional culture, as determined by the increased percentage of CD14+CD206+ and CD64+CD206+ populations in CD11b+ cells. Moreover, the mitochondrial protein p32/gC1qR is expressed in monocytes exposed to U87MG conditioned media. When primary CD14+ monocytes or THP-1 cells are added to previously formed GBM spheroids, both invade and establish within them. However, only primary monocytes differentiate and acquire a clear M2 phenotype characterized by the upregulation of CD206, CD163, and MERTK surface markers on the CD11b+CD14+ population and induce alterations in the sphericity of the cell cultures. Conclusion: our results present a new physiologically relevant model to study GBM/macrophage interactions in a human setting and suggest that both soluble GBM factors, as well as cell-contact dependent signals, are strong inducers of anti-inflammatory macrophages within the tumor niche.